Using a Panel of Experts to Enrich Planning of Distance Education - Goho, James; MacAskill, Pamella; McGeachie, Paul (International Journal of E-Learning & Distance Education / Revue internationale du e-learning et la formation à distance, 2007)
This article describes the results of a qualitative study of a panel of experts in distance education. The panel was selected to help identify directions for the continuing progress of distance education at a large Canadian comprehensive community college. The results identified a number of issues to address in the development of a distance/distributed learning strategy. Four major themes emerged from the interviews: the effect of new telecommunications technologies, the increasing numbers of and changing characteristics of distance education learners, the needs of faculty, and the many-layered adjustments required in educational institutions. These themes facilitated robust internal college consultations. Cet article décrit les résultats d’une étude qualitative d’un panel d’experts en formation à distance. Le panel a été choisi pour aider l’identification d’orientations pour le progrès continu de la formation à distance dans un grand collège communautaire polyvalent canadien. Les résultats décrivent un bon nombre de questions à aborder lors du développement d’une stratégie d’apprentissage à distance ou distribué. Quatre grands thèmes ont émergés des entrevues : l’effet des nouvelles technologies de communication, le nombre croissant et changeant des caractéristiques des apprenants en formation à distance, les besoins du corps enseignant et les ajustements requis à plusieurs niveaux dans les établissements d’enseignement. Ces thèmes ont suscité de sérieuses consultations internes dans les collèges.